Effectiveness of Implementation Teams in Enforcing Minimum Service Standards Policies in Provinces and Regencies/Cities Across Papua - Lutfi Firmansyah (CV. Publikasi Indonesia, 2025)
Basic mandatory affairs or better known as Minimum Service Standards are the Government's efforts in realizing community welfare through service indicators that have been determined through policy regulations, namely Education, Health, Public Works, Public Housing, Trantibumlinmas and Social. However, there are still problems in the implementation of the policy because the policy implementing actors are still not optimal in the implementation of coordination which should be represented in the SPM implementation team which is legalized through a Regional Head Decree. Tanah Papua is an object of discussion in the effectiveness of the coordination team because there are still many provinces and districts/cities that have not formed SPM implementation teams, which can be a potential problem in implementing SPM in Tanah Papua. Transaction cost theory analysis is the basis of the research, supported by opinions from Provincial and District/City stakeholders according to factual conditions in Papua. The result of this policy paper is that a strong coordination commitment and reduced sectoral ego will optimally reduce transaction costs in SPM implementation, although transaction costs in coordination cannot be eliminated but can be reduced. The policy recommendations in this paper are that Regional Heads, Deputy Regional Heads and Regional Secretaries as well as Heads of Regional Apparatus Organizations who are members of the SPM implementation team in Papua can formulate SPM policies for the people in their areas.